2019
DOI: 10.1093/cercor/bhz227
|View full text |Cite
|
Sign up to set email alerts
|

AMPA Induces NO-Dependent cGMP Signals in Hippocampal and Cortical Neurons via L-Type Voltage-Gated Calcium Channels

Abstract: The nitric oxide (NO)/cGMP signaling cascade has an established role in synaptic plasticity. However, with conventional methods, the underlying cGMP signals were barely detectable. Here, we set out to confirm the well-known NMDA-induced cGMP increases, to test the impact of AMPA on those signals, and to identify the relevant phosphodiesterases (PDEs) using a more sensitive fluorescence resonance energy transfer (FRET)-based method. Therefore, a “knock-in” mouse was generated that expresses a FRET-based cGMP in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 76 publications
2
22
0
Order By: Relevance
“…The latter was demonstrated by using transgenic mice ubiquitously expressing a Förster resonance energy transfer (FRET)-based cGMP indicator to analyze the cGMP responses induced by NO or glutamatergic agonists in cultured hippocampal and cortical neurons. In this study, besides the well-established NMDA-induced cGMP responses, the glutamatergic agonist AMPA independently elicited cGMP signals in hippocampal and cortical neurons by triggering L-type VGCC-dependent Ca 2+ influx [122]. This finding is consistent with previous studies demonstrating that nNOS can be activated by Ca 2+ influx through VDCCs [123] and CP-AMPARs [124].…”
Section: Protein-protein Interactionssupporting
confidence: 92%
See 2 more Smart Citations
“…The latter was demonstrated by using transgenic mice ubiquitously expressing a Förster resonance energy transfer (FRET)-based cGMP indicator to analyze the cGMP responses induced by NO or glutamatergic agonists in cultured hippocampal and cortical neurons. In this study, besides the well-established NMDA-induced cGMP responses, the glutamatergic agonist AMPA independently elicited cGMP signals in hippocampal and cortical neurons by triggering L-type VGCC-dependent Ca 2+ influx [122]. This finding is consistent with previous studies demonstrating that nNOS can be activated by Ca 2+ influx through VDCCs [123] and CP-AMPARs [124].…”
Section: Protein-protein Interactionssupporting
confidence: 92%
“…Moreover, the blockade of calcium-permeable AMPARs with PhTx-433 reduced the NO production [121], which directly indicates the dependence of NOS on free calcium ions entering not only through the NMDA channels but also through the calcium-permeable AMPARs. This AMPAR-induced calcium influx probably occurs through L-type voltage-gated calcium channels (VDCC) [122]. The latter was demonstrated by using transgenic mice ubiquitously expressing a Förster resonance energy transfer (FRET)-based cGMP indicator to analyze the cGMP responses induced by NO or glutamatergic agonists in cultured hippocampal and cortical neurons.…”
Section: Protein-protein Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitric oxide (NO), a small gaseous signaling molecule, and its metabolites are widely accepted as important mediators of neurogenic inflammation and neuroinflammation involved in migraine, and these processes are mainly mediated by the NO-cGMP pathways, glutamatergic pathway and NF-κB pathway. Therefore, NTG, a NO-donating agent, has been recognized as a translational model that has been strongly implicated in the pathological mechanisms of migraine [22]. In human subjects, NTG-induced migraine is associated with an increase in the plasma CGRP concentration [27]; increased levels of CGRP, SP and PACAP were also reported in the plasma of rodents treated systemically with NTG [7,26,29].…”
Section: Introductionmentioning
confidence: 99%
“…Abundant reports have indicated that neurogenic inflammation caused by NTG-induced neural activation leads to migraine-like behavior and an increased sensitivity to pain in an NTG model. NO released from NTG initiate a rather slow process that likely involves the activation of the trigeminovascular system in the dura mater and the subsequent activation of trigeminal fibers and the trigeminal nucleus caudalis (TNC) [22]. Furthermore, the NTG-induced increase in NOS activity is implicated in higher basal CGRP levels and might activate the exudation of blood material synergistically, leading to neurogenic inflammation involving the NF-κB pathway [33,54].…”
Section: Introductionmentioning
confidence: 99%